Female Drug Enforcement Officers’ Perceptions and Experiences in the Drug-Law Enforcement World - Abad, Katryn Gaye J. (CV. Literasi Indonesia, 2023)
This qualitative phenomenological study focused on the lived experiences of female drug enforcement officers in the drug enforcement field. Using quota sampling, ten female drug enforcement officers of PDEA ROXII were the participants of the study. The feminist theory helped to clarify the constructed meanings the women attached to their experiences. In-depth interviews were conducted, and the data analysis was guided by the Stevick-Colaizzi-Keen method. The findings revealed that all of the women pursued law enforcement careers because of job security, influence from family and friends, and the desire to help the country solve the problem of illegal drugs. Their job satisfaction was influenced by the successful performance of their duties through the arrest of high-value targets, a conviction of drug personalities, and their perception that they have a challenging and exciting job. Physical and physiological barriers, safety and security, number of cases handled, and desire to practice their professions also influenced their careers. This study revealed that there is gender equality perceived by the female drug enforcers in PDEA ROXII. The differences in roles and their exemptions in certain situations in the conduct of anti-illegal drug operations were not perceived as inequality but more as special treatment and protection of their male counterparts to them. This study contributes to social change by raising awareness about the current status, concerns, and accomplishments of women in law enforcement. Additionally, findings may assist police administrators and legislators in creating policies and procedures that incorporate the needs of female drug enforcement officers.